Factors Associated with Traffic Police Officers’ Knowledge in Providing First Aid to Accident Victims - T. Abdur Rasyid; Bayu Saputra; Rani Lisa Indra; Sandra Sandra; M Lizky Rinaldy (LP3M Universitas Muhammadiyah Tasikmalaya, 2025)
First aid is an immediate and temporary intervention provided at the scene before advanced medical assistance becomes available. Traffic police, as trained lay responders, play a critical role in emergency situations, particularly in traffic accidents. This study aimed to identify factors associated with traffic police officers’ knowledge of providing first aid to accident victims. A quantitative method with a descriptive-analytic design and a cross-sectional approach was employed. The sample consisted of 50 traffic police officers from the Pekanbaru Police Department, selected through consecutive sampling. Data were collected using a structured questionnaire assessing knowledge and attitudes toward first aid. The results showed that the majority of respondents were aged 26–39 years (82.0%) and had higher education (52.0%). Most had not received additional training (78.0%), and 60.0% had provided assistance to accident victims in the past two years. A total of 58.0% of respondents demonstrated good knowledge. The most significant factors influencing knowledge were additional training (p=0.016; OR=10.526) and higher educational attainment (p=0.025; OR=3.800). These findings underscore the importance of supplemental training and the integration of first aid content into formal police education. Practice-based and simulation-based training programs are recommended as effective strategies to enhance practical skills and strengthen the role of police officers as lay first responders in emergency situations.